Detection and characterisation of short fatigue cracks by inductive thermography. Issue 4 (8th August 2022) - Oswald-Tranta, Beate
ABSTRACT: Inductive thermography can be excellently used to detect surface cracks in metals. A short induction heating pulse (0.1-1s) induces eddy currents in the sample and an infrared camera records the surface temperature distribution. As cracks disturb the eddy current distribution and the heat diffusion, they become visible in the infrared images. In this paper it is investigated, how different parameters influence the surface pattern around short cracks (0.5-12mm length). The main emphasis is on finite element simulations, but some experimental results are presented, too. The influence of crack geometry, as crack depth, length, inclination angle and crack shape below the surface are investigated for ferro-magnetic and austenitic steel. Around the crack tips high temperature 'hot spots' can be observed, which intensity increases with the crack depth. But this intensity is strongly affected by the crack shape, whether it is rectangular, trapezoid or half-penny shape. For longer cracks (6-8mm length) simulation results show, that in the middle of the crack the phase distribution can be used to estimate the crack depth. Furthermore, the effect of experimental parameters, as excitation frequency, heating pulse duration and the angle between crack line and induction coil are investigated in order to optimize an experimental setup.